2004
DOI: 10.1161/01.hyp.0000116220.39793.c9
|View full text |Cite
|
Sign up to set email alerts
|

l -Arginine Depletion in Preeclampsia Orients Nitric Oxide Synthase Toward Oxidant Species

Abstract: Abstract-Less nitric oxide (NO)-dependent vasodilation and excess formation of reactive oxygen species could explain poor placenta perfusion in preeclampsia, but the pathways involved are unknown. We tested the hypothesis that reduced NO activity and increased oxidative stress in preeclamptic placenta is related to a low bioavailability of L-arginine. Placental endothelial NO synthase (ecNOS) expression (by immunoperoxidase) and activity (by diaphorase and [ 3 H]L-citrulline formation) were comparable in normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 37 publications
4
106
0
5
Order By: Relevance
“…Much of the uncertainty in this area of research originates from the difficulty in directly assessing the activity of the NO system in the clinical setting. Recently, Noris et al 34 suggested that L-arginine depletion, caused by arginase II overexpression, may orient NO synthase toward oxidant species in placenta in preeclampsia. In addition, McCord and colleagues 35 reported that a relative deficiency of arginine in peripheral blood mononuclear cells may favor superoxide and peroxynitrite production and contribute to oxidative and nitrosative stress in preeclampsia.…”
Section: Potential Mediators Of Endothelial Dysfunction Nitric Oxidementioning
confidence: 99%
“…Much of the uncertainty in this area of research originates from the difficulty in directly assessing the activity of the NO system in the clinical setting. Recently, Noris et al 34 suggested that L-arginine depletion, caused by arginase II overexpression, may orient NO synthase toward oxidant species in placenta in preeclampsia. In addition, McCord and colleagues 35 reported that a relative deficiency of arginine in peripheral blood mononuclear cells may favor superoxide and peroxynitrite production and contribute to oxidative and nitrosative stress in preeclampsia.…”
Section: Potential Mediators Of Endothelial Dysfunction Nitric Oxidementioning
confidence: 99%
“…At least 8 -10 fields per section were examined. The final score per section was calculated as a weighted mean (38).…”
Section: Preparation Of the Tir8 Riboprobe And Nonisotopic In Situ Hymentioning
confidence: 99%
“…Several groups have reported alterations in cytokines/growth factors/chemicals such as TNF-␣, IL-6, IL-1␣, IL-1␤, Fas ligand, oxidized lipid products, neurokinin-B, and asymmetric dimethyl arginine (ADMA) that are released by the placenta and/or other maternal sources in preeclampsia (18 -22). Recently, a lower-than-normal L-arginine concentration that is caused by arginase II overexpression and that may redirect placental endothelial nitric oxide (NO) synthase toward peroxynitrite was described in preeclampsia (23).…”
Section: Abnormal Placentation and Placental Ischemiamentioning
confidence: 99%